Revision, Acceptability and Context Theoretical and Algorithmic Aspects - Gabbay, Dov M.; Rodrigues, Odinaldo T.; Russo, Alessandra; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
An important aspect in the formalisation of common-sense reasoning is the construction of a model of what an agent believes the world to be like to help in her reasoning process. This model is often incomplete or inaccurate, but new information can be used to refine it. The study of techniques that achieve this in a rational way is the task of the discipline of belief revision, with which this book is concerned. There are three key elements to the book's approach. Firstly, the methodology of logic by translation. A specific instance of this is the idea of revision by translation. Revision for a foreign logic is done via its translation into a well-known logic, usually classic logic. Secondly, the technique of meta-level/object-level movement, where we bring some operation defined at the meta-level of a logic into its object level. In this book, we bring the operation of deletion to the object level. Finally, through Labelled Deductive Systems, we use the context of the revision to finetune its operation and illustrate the idea through the presentation of various algorithms. The book is suitable for researchers and postgraduates in the areas of artificial intelligence, database theory, and logic.
Background and Overview -- Introducing Revision Theory -- Stepwise Revision Operations -- Iterating Revision -- Structured Revision: Non-linear Methods for Information Change -- Algorithmic Context Revision -- Revision by Translation -- Object-Level Deletion -- Conclusions and Discussions.
Keywords: Computer science; Database management; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Database Management